COMPARISON OF THE FUEL CALORIFIC VALUE FROM PLASTIC PYROLYSIS WITH COMMERCIAL FUEL - Dianta Mustofa Kamal (Polinema Press, Politeknik Negeri Malang, 2022)
Plastic, which is originated from petrolum, is possible to turn it to alternative fuel. Moreover in 2008, the estimated amount of midden in Indonesia reached 38.5 million tons per year with the largest compositions are organic waste (58%), waste plastics (14%), waste paper (9%) and wood waste (4%) (Ministry of Environment, 2008). Meanwhile in Depok City, the amount of waste which goes to Depok City’s landfill waste is 350-400 tonnes / day (Head of Technical Unit Landscape Depok City Sanitation Department, 2012). From the data, above, can be confirmed using plastic waste as an alternative fuel can be superior because plastic waste is the raw material which is cheap, easily processed, and can reduce environmental pollution. The processing of plastic waste into fuel conversion is done using a plastic waste machine with a continuous system, the working principle of heating at high temperature. Tests which are conducted in this study is to test the octane rating by bomb calorie meter, test anylizer gas emissions, and test octane gas chromatography. Plastic waste fuel, which is the outcome from plastic waste conversion machine with continuous system, can be used as fuel for vehicles, it is because the plastic oil calorific value 10 519 cal / g equivalent calorific value premium. This research is expected to address the scarcity of fossil fuels, and increasing public awareness of using alternative fuel, especially plastic waste fuel.